A Novel Dynamic Overmodulation Strategy of Direct Torque Control - Auzani Jidin; Tole Sutikno; Aiman Zakwan Jidin; Nik Rumzi Nik Idris; Abdul Halim Mohd Yatim (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2010)
The direct torque control-space vector modulation (DTC-SVM) is well-known for achieving excellent dynamic overmodulation. However, the method uses complicated predictive stator flux vector control and requires high precision stator flux vector to define overmodulation mode. This paper proposes a straightforward dynamic overmodulation method and constant switching frequency controller without SVM to obtain a faster dynamic torque response in DTC for induction machines. To perform this method, the flux error status produced from the flux hysteresis comparator during dynamic condition is modified slightly before being fed to the look-up table. The verification of proposed method was performed using MATLAB/Simulink simulation package. The effects of different switching and operating condition on dynamic torque performance are analyzed. The result shows that a faster torque response is achieved in proposed dynamic overmodulation DTC method. The main benefit of the proposed method is its simplicity since only minor modification is made to the basic DTC hysteresis-based structure.